2005
DOI: 10.1002/ar.a.20166
|View full text |Cite
|
Sign up to set email alerts
|

Finite‐element modeling of the anthropoid mandible: The effects of altered boundary conditions

Abstract: Finite-element modeling provides a full-field method for describing the stress environment of the skull. The utility of finite-element models, however, remains uncertain given our ignorance of whether such models validly portray states of stress and strain. For example, the effects of boundary conditions that are chosen to represent the mechanical environment in vivo are largely unknown. We conducted an in vitro strain gauge experiment on a fresh, fully dentate adult mandible of Macaca fascicularis to model a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 27 publications
5
81
2
Order By: Relevance
“…Consequently, there is a need to assess the effects of changes in the orientation of muscle vectors on the FEA results. Again, previous work with a macaque mandible showed that changing the orientation of external forces has a significant effect on FEA results (Marinescu et al, 2005).…”
Section: Muscle Forcesmentioning
confidence: 84%
See 4 more Smart Citations
“…Consequently, there is a need to assess the effects of changes in the orientation of muscle vectors on the FEA results. Again, previous work with a macaque mandible showed that changing the orientation of external forces has a significant effect on FEA results (Marinescu et al, 2005).…”
Section: Muscle Forcesmentioning
confidence: 84%
“…This result can be explained by the fact that the inclusion of PDL as compliant material effectively creates large holes in the mandibular corpus, which reduces the second moment of inertia of the corpus and lowers its neutral axis under bending (Marinescu et al, 2005;Daegling et al, 2008;Gr€ oning et al, 2011a). It is also likely that the polar moment of inertia is reduced so that resistance to torsion decreases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations